PRODUKTIVITAS DAN BEBAN KERJA OPERATOR GERGAJI RANTAI, PADA KEGIATAN PENEBANGAN POHON BERBANIR TINGGI DI HUTAN ALAM DI KALIMANTAN TENGAH - Maraan Mansyur Idris; Soenamo Soenamo (Jurnal Penelitian Hasil Hutan, 1991)
In general, there are three basic  types/methods  of  chain saw operator's body position  in doing mechanical tree felling in natural forest i.e; felling with squat, felling with standing in deeply bending forward and standing while both arms in extreme position  in the soulder joint.  However, the body Position of chain saw operator in high buttress tree felling are usually in standing while both arms in extreme position in the shoulder joint.The extreme  body position  above does not  only  generate static  muscular load  cauaing early fatique and  pain in the shoulder joint  (Hagberg, et al,  1987) but also cause physiological load during work (Ayaz,.1987).   For this matter, a  study   was conducted  for  the  improvement  of  worker's productivity  and  workstress by introducing a new methbd of body position's felling technique.The investigation took place at Central Kalimantan in 1989. The results of this research as follows:1.From faal variable point of view, the chain saw operator's workstress during work is higher than the limited works-tress level recommended by international medical opinion.2.New  felling technique applied on  high buttress tree of  150 to 300 cm can reduse workstress rate about 3-8 beats/min.  While, if  it  is  applied on high buttress tree of > 300 cm causes the operator chain saw's workstres about 1-4  beats/min lower than operator chain saw's workstress. in felling of tree with conventional method.3.Productivity rote with new felling method applied on buttrea  high of 150 cm -  300 cm and > 300 cm are about 19.298rm3/hr and 18.207  m3/hr. The productivity rate with conventional method applied on high buttress of 15’0 cm -300  and> 300 cm are 22.974 m3/hr and 24.974 m.3/hr.4.Altliough the use of new method  on high buttrea  tree felling causes negative effect in work productivity  but in fact it can increasethe forest wood utilization.about  2.63% -4.27%.